Clinical simulation as a Nursing Fundamentals teaching method: a quasi-experimental study - Campanati,Fernanda Letícia da Silva (2022)
ABSTRACT Objectives: to evaluate students’ knowledge gain after the implementation of clinical simulation in Nursing Fundamentals disciplines. Methods: a quasi-experimental intervention was carried out with 60 students, distributed in comparison and intervention groups, who underwent traditional teaching and traditional teaching associated with simulated teaching, respectively. Pre-test and post-test instruments were applied to both groups. Results: after analyzing the students’ performance through the applied instruments, both groups had a cognitive evolution along with the taught content, however, when compared, the intervention group obtained a higher knowledge gain than the comparison group (p = 0.016), demonstrating progressive and increasing improvement with the use of the methodology. Conclusions: simulated teaching significantly helps students in gaining technical-cognitive knowledge. Therefore, it is recommended to adhere to the use of this methodology for teaching Nursing Fundamentals.